Isolation of Withaferin-A from Withania somnifera Dun Leaves and itsAntibacterial Activity - Shashidara, S.; Ashoka Babu, V.L.; Dhanapal, R.; Shahnazbanu (Asian Journal of Chemistry, 2010)
Withaferin-A is a steroidal alkaloid with an unsaturated lactone obtained as an important constituent of Withania somnifera Dun. A new method, was developed for the isolation of withaferin-A from methanolic extract of Withania somnifera Dun leaves. The isolated compound was compared and confirmed with standard withaferin-A by using thin layer chromatography and various spectroscopic techniques (HPLC, UV-spectroscopy and IR). It was found that the method developed was simple, faster, easy to perform and reproducible. Further the isolated compound was screened for its antibacterial activity. The isolated compound showed significant activity when compared with standard streptomycin sulphate.